The Effect of Brain Teaser Games on the Attention of Players Based on Hormonal and Brain Signals Changes - Aliyari, Hamed; Sahraei, Hedayat; Golabi, Sahar; Kazemi, Masoomeh; Daliri, Mohammad Reza; Minaei-Bidgoli, Behrouz (Basic and Clinical Neuroscience Journal, 2021)
Introduction: Computer games as an interactive media play a significant role in the cognitive and behavioral health of the players. Computer games have either positive or negative effects on cognitive indices among players. They also directly influence the lifestyle and quality of life of children, adolescents, and young adults. The present study aimed to evaluate the short-term effects of the brain teaser game on players. Methods: Among 45 male volunteers, 40 subjects with an average age of 20 years were recruited and divided into two groups: the experimental group and the control group. All required tests were conducted before and after the intervention (playing the game) on the experimental group. Also, the same tests were performed on the control group, in which the participants were not allowed to play the game. All participants completed a questionnaire comprised demographic characteristics and specific information regarding the game (e.g., game style and hours spent on playing the game). The saliva samples were collected to measure levels of cortisol and α-amylase. The salivary α-amylase (sAA) and cortisol levels were analyzed using the relevant ELISA kits. The cognitive tests were performed using PASAT software before and after the game to assess the perceptual-cognitive abilities of the players. The brain waveforms were acquired by a 14-channel Emotiv brain signal recording device before and after the game. Data analysis was conducted in R and MATLAB software. Results: PASAT test suggested that mental health and sustained attention were significantly improved after the intervention. In addition, the sAA and salivary cortisol levels were significantly higher before the intervention. The results of the brainwave analysis revealed that stress index and attention were significantly higher before the intervention. Conclusion: Findings of the present study suggest that brain teaser games positively influence the central nervous system and activate stress path, leading to changes in brain signals and subsequently improved cognitive elements, such as attention among players.